Hubungan Terpaan Iklan, Intensitas Komunikasi Word Of Mouth Dan Keputusan Pembelian Produk T-Cash - Rayna Ocha; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
In the midst of competition ruling the mobile market (provider) is up and down, causing companies such as Telkomsel to step business strategy development by presenting the first emoney service provider provider in Indonesia called T-Cash. Although the number of TCash subscribers continues to increase, however, based on data obtained from T-Cash Media Update in 2016, it shows that the company's target for the number of T-Cash subscribers still can not be achieved. So it takes continuous effort to attract consumers to use T-Cash products. The purpose of this study is to determine the relationship of advertising exposure and the intensity of word of mouth communication with the purchase decision of T-Cash products. The study population is a T-Cash service user who has been hit by T-Cash ads and talked about T-Cash products for the past month. While, the sample of research taken as many as 100 respondents with age range 18-35 years by using purposive sampling technique. Based on the hypothesis test conducted using Kendall's Tau-b correlation analysis, it shows the result that: Firstly, there is a positive correlation between exposure of advertisement with purchase decision of T-Cash product with value of significance equal to 0.000 and correlation coefficient value 0,755. This shows a very strong relationship with the direction of a positive relationship. The higher the exposure to advertising, the higher the consumer's decision to buy T-Cash products, and vice versa. Second, there is a positive relationship between the intensity of word of mouth communication with the purchase decision of T-Cash product with a significance value of 0,000 and the correlation coefficient of 0.486. The closeness of the relationship obtained strong and the direction of the relationship is positive. This means, the higher the intensity of word-mouth communication of T-Cash products, the higher the consumer's decision to buy T-Cash products, and vice versa. The advice given is that Telkomsel can create ads that have comedy story lines and information about product advantages such as rebates, ease of registration and usage also need to be submitted in TCash ads